STEM teachers' perceptions about pre-service training and their challenges in CLIL classrooms in Kazakhstan - Maximova, Gaukhar (Nazarbayev University Graduate School of Education, 2020)
Since the beginning of the 21st century a global shift from English as a Foreign Language (EFL) to English as a Medium of Instruction (EMI) alongside Content and Language Integrated Language (CLIL) has been taking place in non-anglophone countries. Kazakhstan introduced a CLIL-oriented trilingual policy in 2007 by which STEM subjects must be taught through English. The State Programme for Education Development of the Republic of Kazakhstan for 2011-2020 aims to increase the proportion of teachers lecturing science subjects in English to 15% by 2020. This is the reason why, in the 2019-2020 academic year, this Trilingual Policy became mainstream in secondary education, triggering a need for pre-service teacher training in English. As a result, this need has brought about higher educational institutions putting in place pre-service teacher training programmes with a multilingual track with a view to endowing the educational system with qualified professionals. With this context in mind, this qualitative study aims to explore, on the one hand, the perceptions that graduates from pedagogical institutions with a multilingual track have about pre-service training; and, on the other hand, the challenges they face in CLIL classrooms. Data was collected through semi-structured interviews that were conducted with six participants. The findings revealed that the teachers generally have a positive attitude toward their pre-service training. They tend to associate the pre-service preparation in a multilingual track with English language development, along with better internship and career opportunities. The challenging areas for the teachers included assessment, the language proficiency of their students, a lack of methodological support and the need for regular language practice. This study might be beneficial for researchers, educators and teachers in multilingual education, programme administrators and policymakers who develop the courses of action to successfully implement the Trilingual Policy in Kazakhstan.
Keywords: pre-service training, CLIL, teacher education, Kazakhstan